Sleeping beauty - Knighton, Kate; Costa, Jana Kelly, Alison (Usborne ; EDC London, Tulsa, Okla., 2007)
Enraged at not being invited to the princess's christening, a wicked fairy casts a spell that dooms the princess to sleep for one hundred years